2001
DOI: 10.1159/000047886
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brainstem Neural Activation after Injury to the TMJ Region

Abstract: The basis for a higher prevalence of painful temporomandibular disorders (TMD) among women than men is not known. The present study used Fos-like immunoreactivity (Fos-LI) to quantify the pattern and magnitude of neural activation within the trigeminal brainstem complex of male and female rats caused by acute inflammatory injury to the temporomandibular joint (TMJ) region. Also, Fos-LI was assessed in animals given morphine, a preferential mu opioid receptor agonist, or U50,488H, a selective kappa opioid agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 41 publications
6
57
0
3
Order By: Relevance
“…This is further supported by studies showing enhanced sensitization of neurons in the trigeminal subnucleus caudalis during late proestrus and estrus when estrogen levels decline abruptly (Martin et al, 2007), and a significant dose-dependent influence of estradiol (daily subcutaneous injections of 2 g or 20 g estradiol for three days) on the encoding properties of the nociceptivespecific neurons in lamina I-II in the medullary dorsal horn of ovariectomized female rats (Tashiro et al, 2007). The neurons in laminae I-II at the subnucleus caudalis/C2-junction have been shown to play a critical role in mediating sex differences related to temporomandibular pain (Bereiter, 2001;Bereiter and Okamoto, 2011). Large amounts of ER-expressing neurons are present in these laminae of the trigeminal subnucleus caudalis (Amandusson et al, 1995;Vanderhorst et al, 2005) (Fig.…”
Section: Modulation Of Nociceptive Transmission At the Level Of The Tmentioning
confidence: 99%
“…This is further supported by studies showing enhanced sensitization of neurons in the trigeminal subnucleus caudalis during late proestrus and estrus when estrogen levels decline abruptly (Martin et al, 2007), and a significant dose-dependent influence of estradiol (daily subcutaneous injections of 2 g or 20 g estradiol for three days) on the encoding properties of the nociceptivespecific neurons in lamina I-II in the medullary dorsal horn of ovariectomized female rats (Tashiro et al, 2007). The neurons in laminae I-II at the subnucleus caudalis/C2-junction have been shown to play a critical role in mediating sex differences related to temporomandibular pain (Bereiter, 2001;Bereiter and Okamoto, 2011). Large amounts of ER-expressing neurons are present in these laminae of the trigeminal subnucleus caudalis (Amandusson et al, 1995;Vanderhorst et al, 2005) (Fig.…”
Section: Modulation Of Nociceptive Transmission At the Level Of The Tmentioning
confidence: 99%
“…But the characterization of the afferent inputs from the TMJ has not yet been determined. Acute injury to the TMJ region results in a high density of Fos-positive neurons in the areas including the trigeminal spinal subnucleus caudalis (Vc) and upper cervical cord junction region (Vc/C2) (Hathaway et al, 1995;Bereiter and Bereiter, 2000;Bereiter, 2001). Based on evidence that the Vc/C2 region was excited by mechanical and/or chemical stimulation of the TMJ region, Takeshita et al (2001) concluded that neurons in the lamina I-II in the Vc/C2 region play an important role in mediating pain sensation in TMD.…”
Section: Introductionmentioning
confidence: 99%
“…9 Similar results were also obtained by the TMJ injection of other algogenic agents. 4,6,25 The cause of this lower sensitivity to experimentally induced TMJ nociception in male rats than in female rats as well as the lower prevalence of many pain conditions, 29 including TMJ pain 21 in men than in women, has not as yet been clarified. Although it might be attributed to a pronociceptive effect of ovarian hormones, 6,10,21 an antinociceptive effect of ovarian hormones has also been reported in animal 9 and human 22 studies.…”
mentioning
confidence: 99%